A Carcharodontosaurid tooth from the Hasandong Formation (Lower Cretaceous) of South Korea - Yun, Chan-gyu (Mongolian Geoscientist, 2020)
A large tooth of theropod dinosaur that was recovered from the Hasandong Formation (Lower Cretaceous; Aptian-Albian) in Daedo island, Hadong Couty, South Gyeongsang Province of South Korea is redescribed. Although the tooth was misidentified as a "Prodeinodon"-like megalosaurid theropod at the first time, detailed comparisons with known theropod dentition anatomy strongly indicate that this tooth belongs to an Acrocanthosaurus-like basal carcharodontosaurid theropod. This referral is supported by its combination of large size, ovoid-shaped cervix outline, mesial carina that does not reach the cervix, labially displaced distal carina and large number of denticles. This tooth is different from other carcharodontosaurid teeth from the same formation in several anatomical aspects (e.g., smaller overall size, presence of transverse lines adjacent to the distal carina, presence of interdenticular sulci in distal carina, denticle densities, crown basal ratio), indicating that carcharodontosaurid diversity in the Early Cretaceous of Korea could have been higher, although these differences may represent positional or individual variations. The presence of Acrocanthosaurus-like theropod teeth (e.g., "Prodeinodon", "Wakinosaurus") from early Cretaceous deposits (Valanginian-Cenomanian) of South Korea, Japan, Mongolia and China indicates that North American Acrocanthosaurus atokensis possibly represents a form that immigrated from the Asia.